Synthesis of two isomers of 3-amino-7α-12α-dihydroxy-5β-cholanic acid - Barsuk, D. O.; Kovalenko, S. M.; Барсук, Д. О.; Коваленко, С. М.; Коваленко, С. Н. (Запорізький державний медичний університет, 2015)
Aim. With the aim of differences investigation in physical-chemical properties optimized synthesis of the two stereoisomers of 3-amino-7-12-dihydroxycholanic acid has been performed. Methods and results. As the source compound natural cholic acid was used. 3α-amino-7α-12α-dihydroxy-5β-cholanic acid was obtained in high yield and low number of byproducts.The yield of 3β-amino-7α-12α-dihydroxy-5β-cholanic acid was low because of steric interference and process needed additional treatment stages. Column chromatography was used for cleaning compounds. The structure was studied and confi rmed by NMR method. Significant differences in signals of NMR spectra and physical-chemical properties 3β-amino-7α-12α-dihydroxy-5β-cholanic acid and 3α-amino-7α-12α-dihydroxy-5β-cholanic acid wasn’t found or observed. З метою вивчення відмінностей у фізико-хімічних властивостях здійснили оптимізований синтез двох стереоізомерів 3-аміно-7-12-дигідроксихоланової кислоти. Як вихідну сполуку використали природну холеву кислоту. 3α-аміно-7α-12α-дигідрокси-5β-холанову кислоту отримали з високим виходом і малою кількістю побічних продуктів. Вихід 3β-аміно-7α-12α-дигідрокси-5β-холанової кислоти низький через стеричні перешкоди та потребував додаткових стадій очистки. Для очисткисполук використали колонкову хроматографію. Будову сполук вивчили методами ПМР. Встановили незначну різницю між сигналами ПМР спектрів і фізико-хімічними властивостями 3β-аміно-7α-12α-дигідрокси-5β-холанової кислоти та 3α-аміно-7α-12α-дигідрокси-5β-холанової кислоти. С целью изучения различий в физико-химических свойствах проведен оптимизированный синтез двух стереоизомеров 3-амино-7-12-дигидроксихолановой кислоты. В качестве исходного вещества использована природная холевая кислота. 3α-амино-7α-12α-дигидрокси-5β-холановая кислота получена с высоким выходом и низким количеством побочных продуктов. Выход 3β-амино-7α-12α-дигидрокси-5β-холановой кислоты был низким из-за стерических препятствий и требовал дополнительных стадий очистки. Для очистки соединений использована колоночная хроматография. Строение синтезированных соединений изучено методами ПМР. Установлена незначительная разница в сигналах ПМР спектров и физико-химических свойствах 3β-амино-7α-12α-дигидрокси-5β-холановой кислоты и 3α-амино-7α-12α-дигидрокси-5β-холановой кислоты.
Синтез двох ізомерів 3-аміно-7α-12α-дигідрокси-5β-холанової кислоти
Синтез двух изомеров 3-амино-7α-12α-дигидрокси-5β-холановой кислоты
Keywords: Cholic Acid; Stereoisomers; 3-amino-7α-12α-dihydroxy-5β-cholanic acid; холева кислота; стереоізомери; 3-аміно-7α-12α-дигідрокси-5β-холанова кислота; холевая кислота; стереоизомеры; 3-амино-7α-12α-дигидрокси-5β-холановая кислота